2018
DOI: 10.1103/physreve.97.012121
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced diffusion with abnormal temperature dependence in underdamped space-periodic systems subject to time-periodic driving

Abstract: We present a study of diffusion enhancement of underdamped Brownian particles in 1D symmetric space-periodic potential due to external symmetric time-periodic forcing with zero mean. We show that the diffusivity can be enhanced by many orders of magnitude at appropriate choice of the forcing amplitude and frequency. The diffusivity demonstrates TAD, abnormal (decreasing) temperature dependence at forcing amplitudes exceeding certain value. At any fixed forcing frequency Ω normal temperature dependence of the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 68 publications
1
11
0
1
Order By: Relevance
“…Effective diffusion coefficient as a function of dimensionless temperature. We observe the estimated Deff from numerical simulations of the stochastic differential equation (1) using the parameter values p = 0.25, F = 0.96 and T = 5.16.The inset shows that the diffusion coefficient does not behaves monotonically with the temperature, which is counterintuitive phenomenon previously found in other systems (see for example Refs [9,[27][28][29][30]…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Effective diffusion coefficient as a function of dimensionless temperature. We observe the estimated Deff from numerical simulations of the stochastic differential equation (1) using the parameter values p = 0.25, F = 0.96 and T = 5.16.The inset shows that the diffusion coefficient does not behaves monotonically with the temperature, which is counterintuitive phenomenon previously found in other systems (see for example Refs [9,[27][28][29][30]…”
mentioning
confidence: 76%
“…This phenomenon is important in the sense that it implies a counterintuitive behavior of the particles diffusing in a medium. To be precise, in recent years it has been shown that, in some systems out of equilibrium, an increase in temperature does not implies always an increase in the diffusion coefficient [9,[27][28][29][30][31][32]. In Fig.…”
Section: Particle Current and Diffusion Coefficient For Fast Tiltingmentioning
confidence: 97%
See 2 more Smart Citations
“…В работе [30] в определенном интервале приложенных внешних сил. Этот явление авторы назвали температурно-аномальной диффузией (ТАД) [33][34]. Феномен ТАД связан со слабым нарушением эргодичности в таких системах, поскольку время корреляции экспоненциально стремится к бесконечности при 0 → T .…”
unclassified